Carpal Tunnel Syndrome: A Frequent Pathology in Clinical Practice - Rei, Sofia; Pinto, Ricardo (Gazeta Médica, 2023)
Carpal tunnel syndrome (CTS) is the most frequent compressive mononeuropathy in clinical practice, with a higher prevalence in women. It is manifested by pain and paresthesia in the area of distribution of the median nerve, usually of nocturnal predominance. The diagnosis is based on anamnesis and physical examination, complemented by nerve conduction studies and electromyography. The Phalen and Tinnel tests are provocative maneuvers suggestive of CTS. As for treatment, in mild cases, a conservative approach can be chosen; in moderate to severe cases, or failure of conservative treatment, surgical treatment is indicated. The purpose of this article is to review the main guidelines regarding the approach and treatment of CTS. The family doctor is in a privileged position for the diagnosis and treatment of the clinical manifestations of CTS. All interventions must be carried out to improve patients’ quality of life and obtain health gains. A multidisciplinary approach may be required, through active collaboration between Primary and Secondary Health Care.